THE EFFECT OF GIVING ROSELLA FLOWER (HIBISCUS SABDARIFFA) BREWING ON REDUCING HYPERTENSION IN THE ELDERLY AT THE PEMATANG PANGGANG II PUBLIC HEALTH CENTER - Adhika Wijayanti; Yuli Suryanti; Sartika Dwi Yolanda; Yona Sari; Bramtama Sukma Mulia (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
High blood pressure, or hypertension, occurs when blood pressure rises to unhealthy levels. Blood pressure measurements take into account how much blood passes through the blood vessels and the amount of resistance the heart is putting on the blood vessels. Arteries become less elastic, especially in older adults, as the aging process of the body's cells increases resistance. The narrower the arteries, the higher the blood pressure. Over the long term, elevated blood pressure can lead to health problems, including heart disease. This quantitative study, using a quasi-experimental pretest-posttest design conducted in the working area of ​​Pematang Panggang II Health Center, from April-May 2024. This design was chosen to determine the correlation between the independent variable of the effect of rosella flower decoction, with the dependent variable, namely the decrease in hypertension in the elderly. The study population included all elderly people at Pematang Panggang II Health Center in 2024 with a total of 120 elderly people selected using the purposive sampling technique. purposive sampling and the number of samples in this study was 30 people. Data analysis was carried out univariately and bivariately. Based on the influence test usingWilcoxon Sign Rank It was found that the p value of 0.000 (p < 0.05) showed that there was an effect of giving rosella flower infusion on reducing blood pressure.